IMPLEMENTASI METODE LONG SHORT TERM MEMORY UNTUK MEMPREDIKSI PERGERAKAN NILAI HARGA EMAS - Michael Owen; Vincent Vincent; Riama Br Ambarita; Evta Indra (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
Investment is an activity that is invested or financed with the hope of profit or return in the future. One form of investment is to use gold. Many people are interested in investing in gold. Apart from being quite affordable, investing in gold is also very easy to do and flexible. Gold is included in the low risk investment class because its price movements tend to follow the rate of inflation. This study uses the Long Short Term Memory (LSTM) method to predict the movement of gold prices which will visualize the data in the form of a Line Chart. This study aims to provide decision support material regarding the movement of buying and selling prices of gold through the presentation of data aimed at people who invest in gold. However, real gold price movements cannot be separated from external factors such as the exchange rate of the rupiah against foreign currencies, import export policies and other government policies. There are many influencing factors such as opening price, closing price, adjust close, volume, highs, lows recorded over a certain period of time. Another factor is the Daily Return which can be positive (Grown In Value) and negative (Lost In Value).